2017
DOI: 10.4103/ojo.ojo_1_2017
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented ciliary body medulloepithelioma in a newborn infant

Abstract: Ciliary body medulloepithelioma is a nonpigmented tumor which presents during the first decade of life. It is rarely seen in newborn infants. We report a pigmented medulloepithelioma in a newborn infant, which showed a rapid growth. Ciliary body medulloepithelioma should be considered in the differential diagnosis in a newborn infant presenting with leukocoria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…In fact, there is no population-based information on incidence and prevalence about medulloepithelioma in literature and only few studies describe this tumor in newborns (as shown in Table 1). 7,8 Our three casesare congenital, with an average age at presentation of 19days, while the age of presentation is commonly between 2 and 10 years of age.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In fact, there is no population-based information on incidence and prevalence about medulloepithelioma in literature and only few studies describe this tumor in newborns (as shown in Table 1). 7,8 Our three casesare congenital, with an average age at presentation of 19days, while the age of presentation is commonly between 2 and 10 years of age.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, there is no population-based information on incidence and prevalence about medulloepithelioma in literature and only few studies describe this tumor in newborns (as shown in Table 1). 7,8…”
Section: Discussionmentioning
confidence: 99%
“…A total of 65 studies involving 97 children with medulloepithelioma of the CB were considered eligible for inclusion in this review and we added our present case, with a total of 98 cases summarized in Table 1 . [ 2 , 4 , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ] The other 3 cases series that were not included in the analysis are summarized in Table 2 for further information […”
Section: Discussionmentioning
confidence: 99%
“…Medulloepithelioma is derived from the nonpigmented CB epithelium with no theoretical barrier preventing the intraocular extension of the tumor to other ocular tissues, especially the pigmented epithelium of the iris that is continuous with the nonpigmented epithelium of the CB [ 12 ], and foci of intrinsically pigmented tumor cells are relatively common [ 9 , 76 ]. Recently, a tumor derived from the pigmented CB epithelium was described in a 11-year-old child [ 2 ] and in a newborn [ 62 ]. Medulloepithelioma is composed of proliferating poorly differentiated neuroepithelial cells in clusters with typical intra tumoral cysts and frequent primitive tubules with formation of large empty clefts surrounded by loose mesenchymal tissue rich in hyaluronic acid and peripheral multilayers of columnar cells forming typical rosette-like structures, often larger and more cellular than in retinoblastoma cases [ 8 , 31 , 70 , 73 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Atypical presentation of this child closely mimics medulloepithelioma which presents between 2 and 10 years of age and has been reported in infants as young as 6 months. [ 10 ] Our child presented with combine diffuse infiltration into ciliary body with cataract which is sparsely reported in literature. [ 9 11 ] Treatment of JXG is case based and total surgical excision of lesion is required for extensive lesions.…”
Section: Discussionmentioning
confidence: 99%